Salt Affected Soils of Indo-Gangetic Plains - Prasad, K. G.; Sharma, S. D. (Indian Forester, 1994)
Some salt-affected soils of Indo-gangetic plains were characterised and classified in accordance with Soil Taxonomy Petrocalcic Natrustalf were of wider occurrence and identified in Kurukshetra Forest Division and Gurgaon Social forestry Division, Haryana and Patiala Forest Division, Punjab. However, Typic Natrustalf and Salorthidic Natrustalf also occur in Kurukshetra Forest Division. Aquic Petrocalcic Natrustalf were identified in Kanaksinghpur of Sultanpur District and Khara of Raebraeilly District, Uttar Pradesh. The soils of Rohtak Social Forestry Division, Haryana were classified as salorthidic Natrustalf and Typic Salorthidic on the basis of their characteristics.